When Painting Enhances Architecture: Interventions in a Public Setting - Alcaide Ramírez, Aurora; Ruiz-Abellón, Ana (Proyecto, Progreso, Arquitectura, 2021)
This paper analyses four pictorial interventions carried out in a public setting; painting acts upon architecture in all of them, and occasionally over the road surface and nearby street furniture, achieving a re-signification of the place. The projects chosen (The Museum of Gravity by Krijn de Koning; Color Jam by Jessica Stockholder; Rockaway! by Katharina Grosse; and the intervention at Flax Art & Design by Heather Day) enhance the intervened-upon architecture, and allow for different ways of experiencing and perceiving it. To that end, these proposals are shaped by means of abstract compositions (geometric or gestural-organic) in which colours play the main role, providing the original hues of the architectural environment over which they are applied –usually neutral and without any specific function- with their additional contribution. Among the main conclusions of the study, we should highlight the use of colour in every work for its intrinsic value and for its ability to change the perception of the formal properties of the intervened-upon architecture; the joining of past and present in two of them because of acting on dilapidated or abandoned buildings; the reversibility or ephemeral nature of most projects; the dialogue with the environment; an approach close to tactical urbanism in different ways, and keeping purely decorative approaches at a great distance.